On the pentaquark candidates p+c (4380) and p+c (4450) within the soliton picture of baryons - Scoccola, Norberto Nerio (2016)
Using the bound state version of the topological soliton model for the baryons we show that the existence of a bound (or quasi-bound) D-soliton state leads to the possibility of having hidden charm pentaquarks with quantum numbers and masses, which are compatible with those of the candidates recently reported by the LHCb experiment. The implications of heavy quark symmetry are elaborated.